2021
DOI: 10.1109/access.2021.3086504
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Markovian Jump Systems With Quantized Input and Generally Uncertain Transition Rates

Abstract: This study addresses the stabilization condition for Markovian jump systems with quantized input and generally uncertain transition rates. To stabilize Markovian jump systems with nonlinear inputs using only partial knowledge regarding to the transition rates, the proposed controller is designed as two control parts: a linear control part for stabilizing the system and a nonlinear control part for eliminating undesirable effects from the quantized input. Moreover, an appropriate weighting method, using lower a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Then, using the Schur complement, it can be shown that ( 43) implies (27). Furthermore, from Condition (30), the LMI condition in ( 23) can be obtained by…”
Section: Controller Synthesis With Gutrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, using the Schur complement, it can be shown that ( 43) implies (27). Furthermore, from Condition (30), the LMI condition in ( 23) can be obtained by…”
Section: Controller Synthesis With Gutrsmentioning
confidence: 99%
“…The method reported in Ref. [28] has piqued the interest of researchers [29,30] concerning the stabilization problem of MJSs. These results all focus on the uncertainties of the transition rates, but there is no consideration of external disturbances.…”
Section: Introductionmentioning
confidence: 99%